The Future of English Language Teaching in Pesantren: AI-Driven Personalization and Engagement - Mawardi Mawardi; Ibnu Hajar (International Journal of Education, Language, and Religion, 2026)
This study examines the role of Artificial Intelligence (AI) in English Language Teaching (ELT) at Almuslimun Islamic Boarding School in North Aceh, with a focus on its impact on pedagogy and student learning. Conducted from March to May 2025, the research engaged six English teachers—three from junior high school and three from senior high school—to explore their experiences with AI tools. Using a qualitative approach, data were collected through classroom observations, interviews, and teacher reflection journals, providing insights into how AI enhances ELT. The findings reveal that AI facilitates personalized learning by adapting content to individual student needs, boosts engagement through interactive applications like language-learning chatbots, and improves teaching efficiency via automated assessments and feedback. However, challenges such as limited technological infrastructure, gaps in teacher training, and the need to align AI use with Islamic educational values were also identified. The study underscores the potential of AI to transform language education in religious boarding schools while emphasizing the importance of context-sensitive implementation. Practical recommendations are provided to help educators and policymakers integrate AI effectively, ensuring it complements traditional teaching methods without compromising the school’s cultural and religious ethos. This research contributes to the broader discussion on AI in education, particularly in faith-based institutions, where the adoption of technology must strike a balance between innovation and institutional values.